Enhancing in vitro ruminal digestibility of oil palm empty fruit bunch by biological pre-treatment with Ganoderma lucidum fungal culture - Mohd Yasid, Nur Nazratul Fareha; M. R. M, Rakib; Zailan, Mohamad Zaihan; Yaakub, Halimatun (Public Library of Science, 2021)
The changes in lignocellulosic biomass composition and in vitro rumen digestibility of oil palm empty fruit bunch (OPEFB) after pre-treatment with the fungus Ganoderma lucidum were evaluated. The results demonstrated that the pre-treatment for 2–12 weeks has gradually degraded the OPEFB in a time-dependent manner; whereby lignin, cellulose, and hemicellulose were respectively degraded by 41.0, 20.5, and 26.7% at the end of the incubation period. The findings were corroborated using the physical examination of the OPEFB by scanning electron microscopy. Moreover, the OPEFB pre-treated for 12 weeks has shown the highest in vitro digestibility of dry (77.20%) and organic (69.78%) matter, where they were enhanced by 104.07 and 96.29%, respectively, as compared to the untreated control. The enhancement in the in vitro ruminal digestibility was negatively correlated with the lignin content in the OPEFB. Therefore, biologically delignified OPEFB with G. lucidum fungal culture pre-treatment have the potential to be utilized as one of the ingredients for the development of a novel ruminant forage.